Genotype by Environment Interaction for Yield And Yield Contributing Traits of Finger Millet (Eleusine Coracana) In Bangladesh (Bangladesh Journal of Agricultural Research, 2023)
Stability of for yield and yield contributing traits of finger millet is an important consideration for identification of superior genotypes, which is highly influenced by agro-climatic conditions. The present study was conducted to determine stability for grain yield and yield contributing traits of four finger millet genotypes at three different locations viz; Gazipur, Jamalpur, and Rangpur during 2019-20. In AMMI (Additive Main and Multiplicative Interaction) model, G × E interaction analysis of grain yield and yield contributing traits showed differential interaction of the genotypes in the different environmental conditions. Rangpur and Gazipur were rich for finger millet production while the environment of Jamalpur was poor. Among the genotypes, IE-501 produced the maximum grain yield (5.81 t/ha), followed by IE-2043 (4.69 t/ha) in the favorable environment. Genotypes IE-2043 and IE- 3392 exhibited higher yielding as well as stable over all environments. Considering the AMMI model and mean, bi and S2di, the genotypes IE-2043 and IE-3392 would be suitable across environment whereas genotype IE-501 would be suitable under favorable environmental. For all of the traits evaluated, none of the genotypes were found stable across locations. The genotypes IE- 2043 and IE-3392 with high mean grain yield could be utilized for developing high yielding stable finger millet genotypes.Bangladesh J. Agril. Res. 46(4): 445-455, December 2021